Digital Computer Science for Tax System in SME Taxpayers in Binjai City - Vebry M Lumban Gaol; Halomoan S Sihombing; Henry Lumban Batu (Jurnal Penelitian Pendidikan IPA, 2023)
:  Computer technology with digital power will bring better tax payment procedures and expectations of compliance levels. The digital world will encourage increasingly widespread use of artificial intelligence components to make tax-related work easier. This research falls under comparative causal studies using a survey method. The population consists of MSME operators (individual taxpayers) in the city of Binjai who have filled out and returned the questionnaire to the researchers. The sample selection was carried out using purposive sampling technique, and data was gathered from the opinions or perceptions of MSME operators (individual taxpayers) in Binjai. The primary data obtained were descriptively analyzed, and the model and the influence of tax rates and tax penalties on taxpayer compliance through tax understanding were examined using path analysis. The findings indicate a significant influence of tax rates and tax penalties on taxpayer compliance both simultaneously and partially, with tax understanding as an intervening variable not fully proving to mediate the relationship between tax rates and penalties on taxpayer compliance. The low path analysis value in this study should be considered by subsequent researchers to include other variables that may affect corporate value